Gas exchange - John Dingley (2000)
Inventor:DINGLEY JOHN [GB]Applicant:DINGLEY JOHNCPC:A61M1/1698IPC:A61M1/14A61M1/16(IPC1-7): A61M1/14Publication info:US2004057869 (A1)2004-03-25Priority date:2000-11-28